Longitudinal assessment of serum anticholinergic activity in delirium of the elderly - Munster, Barbara C. van; Kopitz, Jürgen (Journal of psychiatric research, 2012)
Background: Delirium, a frequently occurring, devastating disease, is often underdiagnosed, especially in dementia. Serum anticholinergic activity (SAA) was proposed as a disease marker as it may reflect delirium's important pathogenetic mechanism, cholinergic deficiency. We assessed the association of serum anticholinergic activity with delirium and its risk factors in a longitudinal study on elderly hip fracture patients. Method: Consecutive elderly patients admitted for hip fracture surgery (n = 142) were assessed longitudinally for delirium, risk factors, and serum markers (IL-6, cortisol, and SAA). Using a sophisticated statistical design, we evaluated the association between SAA and delirium in general and with adjustments, but also the temporal course, including the events fracture, surgery, and potential delirium, individual confounders, and a propensity score. Results: Among elderly hip fracture patients 51% developed delirium, these showed more risk factors (p < 0.001), and complications (p < 0.05). Uncontrolled SAA levels (463 samples) were significantly higher in the delirium group (4.2 vs. 3.4 pmol/ml) and increased with delirium onset, but risk factors absorbed the effect. Using mixed-modeling we found a significant increase in SAA concentration (7.6% (95%CI 5.0-10.2, p < 0.001)) per day, which was modified by surgery and delirium, but this effect was confounded by cognitive impairment and IL-6 values. Confounder control by propensity scores resulted in a disappearance of delirium-induced SAA increase. Conclusions: Delirium-predisposing factors are closely associated with changes in the temporal profile of serum anticholinergic activity and thus neutralize the previously documented association between higher SAA levels and delirium. An independent relationship of SAA to delirium presence is highly questionable.